Profesor Marian Walczak (1923–2020)* In memoriam - Chmielewski, Witold (Biuletyn Historii Wychowania, 2020)
Presenting Prof. Marian Walczak’s achievements concentrated on the field of Polish Teachers’ Union and the history of education. The presentation of Prof. Marian Walczak’s biography and achievements in all fields of his rich academic activity, especially in the scope of the history of Polish Teachers’ Union, underground teaching, the activity of high schools and education as well as the martyrdom of Polish teachers during the Nazi occupation. Moreover, the results of the professor’s research into the history of Polish education after WWII have also been presented. The achievements of Prof. Marian Walczak were significant. He is remembered by posterity for his activity in the history of Polish Teachers’ Union and the history of education in the 20th century.